Chemical shift‐based MRI to measure fat fractions in dystrophic skeletal muscle. Issue 1 (4th September 2013) - Triplett, William T.; Baligand, Celine; Forbes, Sean C.; Willcocks, Rebecca J.; Lott, Donovan J.; DeVos, Soren; Pollaro, Jim; Rooney, William D.; Sweeney, H. Lee; Bönnemann, Carsten G.; Wang, Dah‐Jyuu; Vandenborne, Krista; et al.
<x xml:space="preserve">Abstract</x> Purpose The relationship between fat fractions (FFs) determined based on multiple TE, unipolar gradient echo images and 1H magnetic resonance spectroscopy (MRS) was evaluated using different models for fat‐water decomposition, signal‐to‐noise ratios, and excitation flip angles. Methods A combination of single‐voxel proton spectroscopy (1H‐MRS) and gradient echo imaging was used to determine muscle FFs in both normal and dystrophic muscles. In order to cover a large range of FFs, the soleus and vastus lateralis muscles of 22 unaffected control subjects, 16 subjects with collagen VI deficiency (COL6), and 71 subjects with Duchenne muscular dystrophy (DMD) were studied. 1H‐MRS–based FF were corrected for the increased muscle 1H2O T1 and T2 values observed in dystrophic muscles. Results Excellent agreement was found between coregistered FFs derived from gradient echo images fit to a multipeak model with noise bias correction and the relaxation‐corrected 1H‐MRS FFs (y = 0.93x + 0.003; R2 = 0.96) across the full range of FFs. Relaxation‐corrected 1H‐MRS FFs and imaging‐based FFs were significantly elevated (P < 0.01) in the muscles of COL6 and DMD subjects. Conclusion FFs, T2, and T1 were all sensitive to muscle involvement in dystrophic muscle. MRI offered an additional advantage over single‐voxel spectroscopy in that the tissue heterogeneity in FFs could be readily determined. Magn Reson Med 72:8–19, 2014. © 2013 Wiley Periodicals, Inc.